6(x-6)+8=8x+12

Simple and best practice solution for 6(x-6)+8=8x+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-6)+8=8x+12 equation:


Simplifying
6(x + -6) + 8 = 8x + 12

Reorder the terms:
6(-6 + x) + 8 = 8x + 12
(-6 * 6 + x * 6) + 8 = 8x + 12
(-36 + 6x) + 8 = 8x + 12

Reorder the terms:
-36 + 8 + 6x = 8x + 12

Combine like terms: -36 + 8 = -28
-28 + 6x = 8x + 12

Reorder the terms:
-28 + 6x = 12 + 8x

Solving
-28 + 6x = 12 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-28 + 6x + -8x = 12 + 8x + -8x

Combine like terms: 6x + -8x = -2x
-28 + -2x = 12 + 8x + -8x

Combine like terms: 8x + -8x = 0
-28 + -2x = 12 + 0
-28 + -2x = 12

Add '28' to each side of the equation.
-28 + 28 + -2x = 12 + 28

Combine like terms: -28 + 28 = 0
0 + -2x = 12 + 28
-2x = 12 + 28

Combine like terms: 12 + 28 = 40
-2x = 40

Divide each side by '-2'.
x = -20

Simplifying
x = -20

See similar equations:

| k/12=26 | | 2x^2-7x-4x=0 | | 7x-157=113-2x | | 2/5(r-2)=3/30(r-4) | | 5s+6=6s+2 | | 30=5c-3 | | 4d^6*3d^6= | | 9x-6=12x+15 | | 2x+4x-3=15 | | -9x-32=16-12x | | 12p-4=56p | | 17*(-6)= | | 20b=300 | | 5k(6k+7)=0 | | -6*(-8)= | | -203+10x=61-2x | | 12x+5=-45 | | 12-8x(-6)= | | 12e=216 | | 3/4=12/ | | 8a+6a-2=5 | | (7)(-2)= | | 6x-1+9x+8= | | (3x)(49)=(14x) | | -3(2t+3)=-33 | | 85f=685 | | 5v+x=w^2 | | 15p-5p+4=9 | | -10(s+1)=51 | | 0.72*c=7.5 | | 5x-3+2x=7x+7 | | 48/-16= |

Equations solver categories